CARE OF THE CALIFORNIA RED EARTHWORM IN UZBEKISTAN UNDER DIFFERENT FEEDING CONDITIONS (Scientific journal of the Fergana State University, 2025)
Using various types of animal manure, food waste, hay, straw, and other nutrient substrates common in Uzbekistan, high-quality biohumus fertilizer was obtained, fully meeting international standards. Compared with biohumus produced abroad (Russia, Ukraine, Belarus), the obtained biohumus contains 3-5% more humus, 0.2-0.3% more potassium and nitrogen, 4% more ash, the same amount of phosphorus, and 16 additional microelements (which were absent in local biohumus). Additionally, it was shown that 1 mm³ of biohumus contains vitamins, biostimulants, and 2.5-3 billion microorganisms. It is known that the composition of humus depends on the composition of the substrate consumed by worms: manure from animals fed with concentrated feed is rich in organic matter and allows for the production of high-quality biohumus. For this reason, the most suitable nutrient medium was selected for worm breeding.